Parallel evolution of methyltransferases leads to vobasine biosynthesis in Tabernaemontana elegans and Catharanthus roseus - Farzana, Maisha; Richardson, Matthew Bailey; Deschênes, Daniel André Ramey; Mai, Zhan; Njoku, Destiny Ichechi; Deslongchamps, Ghislain; Qu, Yang (Frontiers in Plant Science, 2024)
Monoterpenoid indole alkaloids (MIA) are one of the largest and most complex alkaloid class in nature, boasting many clinically significant drugs such as anticancer vinblastine and antiarrhythmic ajmaline. Many MIAs undergo nitrogen N-methylation, altering their reactivity and affinity to the biological targets through a straightforward reaction. Remarkably, all known MIA Nmethyltransferases (NMT) originate from the neofunctionalization of ancestral γ-tocopherol Cmethyltransferases (γTMTs), a phenomenon seemingly unique to the Apocynaceae family. In this study, we unveil and characterize a new γTMT-like enzyme from the plant Tabernaemontana elegans (toad tree): perivine Nβ-methyltransferase (TePeNMT). TePeNMT and other homologs form a distinct clade in our phylogenetic study, setting them apart from other γTMTs and γTMT-like NMTs discovered to date. Enzyme kinetic experiments and enzyme homology modeling studies reveal the significant differences in enzyme active sites between TePeNMT and CrPeNMT, a previously characterized perivine Nβ-methyltransferase from Catharanthus roseus (Madagascar periwinkle). Collectively, our findings suggest that parallel evolution of ancestral γTMTs may be responsible for the occurrence of perivine N-methylation in T. elegans and C. roseus.